Blautia argi sp. nov., a new anaerobic bacterium isolated from dog faeces. Issue 1 (8th November 2018) - Paek, Jayoung; Shin, Yeseul; Kook, Joong-Ki; Chang, Young-Hyo
Abstract : Two isolates of a Gram-positive, non-motile, coccoid or oval-shaped anaerobic bacterium, designated strains N6H1-15 T and YH1_16, were isolated from faecal samples obtained from a mature dog. Analysis of 16S rRNA gene sequences indicated that the isolates belonged to the Blautia coccoides rRNA gene group (cluster XIVa) and were closely related to Blautia hansenii KCTC 5951 T, Blautia stercoris KCTC 5981 T, Blautia producta producta KCTC 3695 T and B. coccoides DSM 15327 T, with 96.7, 94.4, 94.2 and 93.9 % sequence similarity, respectively. The two isolates contained m -diaminopimelic acid within their peptidoglycans. The major polar lipids were diphosphatidylglycerol and phosphatidylglycerol, and the major fatty acids were C16 : 0 (18.5 %), C16 : 0 (18.0 %) and C18 : 1 cis 9 (16.2 %). The predominant metabolic end products of glucose fermentation were acetic and lactic acids, and the G+C content was 44.2 mol%. Thus, the polyphasic data suggest that the two new isolates represent a new species, proposed as Blautia argi sp. nov. The type strain is N6H1-15 T (=KCTC 15426=JCM 31394).